PEDAGOGIK KRITIS BERBASIS DIGITAL LEARNING DAN BIG DATA UNTUK MENINGKATKAN LITERASI DIGITAL PENDIDIK DI KABUPATEN INDRAMAYU - Babang Robandi; Rusman Rusman; Ocih Setiasih; Wawan Setiawardani (Abdimas Siliwangi, 2022)
Education must be able to adapt and develop according to the times. Now we are treading the era of the industrial revolution 4.0, known as the era of digitalization in various sectors of life, including the education sector. The influence that occurs, among others, in digital literacy skills. Smartphone penetration of Indonesia's population is quite large. This service is a development of the research that has been done on critical awareness and pedagogic competence. The pedagogic competence of educators in Indramayu district from the report from the Ministry of Education and Culture is still at a score of 52, and is ranked 20th in Indonesia. This activity is a solution that can be offered. Through the development of critical pedagogic competencies of digital-based educators and the use of big data, it is hoped that an effective education and mentoring can be created. The method of community service through descriptive studies using a qualitative approach by revealing data based on the research formulation questions, namely how to implement critical pedagogics based on digital learning and big data to improve educators' digital literacy? the training system is carried out using an e-course platform. Participants who receive further information register online and log in to access content, discuss with other participants and work on the learning evaluation that has been provided. From the results of these activities, 70% of the 223 participants were able to answer the questions correctly.